ASPECTOS HEMATOLÓGICOS E REGULAÇÃO DO METABOLISMO DO FERRO NA PARACOCCIDIOIDOMICOSE - Eliana da Costa Alvarenga de Brito (2022)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by fungi of the genus Paracoccidioides spp. that can cause hematological and iron metabolism changes and are related to the inflammatory response of the host. Thus, anemia, leukocytosis, eosinophilia, and lymphocytosis have been described, mainly in the acute/subacute form of the disease. The hematological and iron metabolism changes in the chronic form of PCM are poorly understood. This study aimed to analyze and interpret hematological aspects and iron metabolism in different compartments and evaluate serum hepcidin in patients with chronic PCM during the curing process. The study was carried out at the Hospital Dia Professora Esterina Corsini at the Federal University of Mato Grosso do Sul. Individuals of both sexes, diagnosed with chronic PCM between 2013 and 2021, participated in the study. Three studies were carried out. The first study, to contribute to the knowledge about changes in hematological cells in the chronic form of PCM and monitoring of treatment, it was evaluated the blood count of patients with chronic PCM before initiation and during different stages of treatment. The 62 patients included had a mean age of 54.3 years (SD 6.9) and were predominantly men (96.8%) and rural workers (88.7%). The changes in the blood count were mainly anemia and monocytosis, however, the changes are not exuberant. After treatment, especially when a clinical cure is achieved, most hematological indices change significantly, reflecting the interference of infection in these parameters. The second study, to understand which and how intense the disturbances in iron metabolism in patients with the chronic form of PCM, it was analyzed the different iron compartments before treatment and after clinical cure. It was noted that PCM changes the storage and functional compartments of the iron, without changing the transport compartment. Although, before treatment the central measurements (mean or median) of ferritin, hemoglobin, erythrocytes, hematocrit, and serum iron were normal, there was a reduction in ferritin levels and an increase in other parameters between the start of treatment and clinic cure. In addition, it was observed that changes in iron storage and functional compartments were associated with the severity of the disease. A negative correlation between C-reactive protein and functional compartment parameters was observed. Thus, it was possible to infer that PCM interferes with iron metabolism by transferring iron from the functional compartment to the storage compartment, characterizing anemia or inflammation. The third study analyzed the serum hepcidin levels of patients with the chronic form of PCM before and during treatment and correlated hepcidin with parameters of iron metabolism and with blood cells. Despite the increase in hemoglobin and iron and decrease in ferritin observed between pretreatment and clinical cure, there was no reduction in hepcidin levels, as expected. However, a direct correlation was observed with leukocyte cells (r = 0.483; p = 0.001), neutrophils (r = 0.418; p = 0.006), and monocytes (r = 0.396; p = 0.009) two phagocytic cells that act in first-line defense of PCM and are known to produce hepcidin. In summary, the chronic form of PCM is associated with changes in iron metabolism and in hematological cells, which are generally associated with the severity of the disease and improve after treatment.